2015
DOI: 10.1152/jn.00764.2014
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate receptors in the hypothalamic paraventricular nucleus contribute to insulin-induced sympathoexcitation

Abstract: Stocker SD, Gordon KW. Glutamate receptors in the hypothalamic paraventricular nucleus contribute to insulin-induced sympathoexcitation. J Neurophysiol 113: 1302-1309, 2015. First published December 4, 2014 doi:10.1152/jn.00764.2014.-The sympathoexcitatory response to insulin is mediated by neurons in the arcuate nucleus (ARC) and hypothalamic paraventricular nucleus (PVH). Previous studies have reported that stimulation of ARC neurons increases sympathetic nerve activity (SNA) and arterial blood pressure (AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…Indeed, we found that KYN also reduced the stimulatory effects of leptin on LSNA and baroreflex function, implicating a glutamatergic input to the PVN in the leptin responses. Nevertheless, like SHU9119, while our dose of KYN largely reversed the sympathoexcitatory effects of iv insulin, 34 it only partially reduced the effects of leptin. Moreover, the combined effects of SHU9119 and KYN did not produce a greater effect than either alone.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Indeed, we found that KYN also reduced the stimulatory effects of leptin on LSNA and baroreflex function, implicating a glutamatergic input to the PVN in the leptin responses. Nevertheless, like SHU9119, while our dose of KYN largely reversed the sympathoexcitatory effects of iv insulin, 34 it only partially reduced the effects of leptin. Moreover, the combined effects of SHU9119 and KYN did not produce a greater effect than either alone.…”
Section: Discussionmentioning
confidence: 63%
“…24, 42 Both α-MSH and glutamatergic inputs into the PVN are involved. 31, 34 Because insulin and leptin are often increased together, such as after a meal or in insulin resistant individuals, these parallel pathways may converge and amplify sympathoexcitatory effects. Moreover, because the effects of leptin 4 and insulin 31, 33, 43 to increase the activity of various sympathetic nerves are diverse, relative increases in leptin versus insulin may homeostatically and differentially engage increased sympathetic outflow to several organ beds.…”
Section: Discussionmentioning
confidence: 99%
“…We did not detect a statistically significant increase following insulin in those same regions. Although, the PVN and RVLM are believed to be involved in mediating the sympatho-excitatory effects of hyperinsulinemia, microinjections of insulin directly into those brain nuclei did not induce an increased sympathetic nerve activity suggesting there is no direct activation of insulin receptors in those brain nuclei (Bardgett et al, 2010; Ward et al, 2011; Stocker and Gordon, 2015). Since we found that insulin alone increased RSNA, it was perhaps, surprising that we did not detect an increase in Fos in those regions.…”
Section: Discussionmentioning
confidence: 99%
“…Within the ARC, POMC and AgRP neurons are known to be equipped with the insulin receptor (63). These neurons may provide the melanocortinergic drive and/or glutamatergic neurotransmission to the paraventricular nucleus that have been implicated in mediating the sympathoexcitatory effects of insulin (64;65). …”
Section: Insulin Acts In the Arc To Increase Sympathetic Outflowmentioning
confidence: 99%